Keluarga dalam Perspektif Agama dan Sains - Efi Nurjanah (Asy-Syari’ah : Jurnal Hukum Islam, 2017)
The family is the first environment for children, the family environment first of all the children get the influence. Therefore, the family is the oldest educator who is natural. The birth of the family as an educational institution since humans exist, and the task of the family is to lay the foundations for the development of children, so that children can develop well. One of the most important goals of family formation to meet the needs of children’s love. Instinct loves the child is the potential created by Allah along with the creation of man. Parents are obliged to maintain the nature of the child so as not to do deviations. The sense of affection and tranquility shared in the family will make the child grow and thrive in a happy atmosphere. The happiness will in turn give the child confidence, peace, love, and distance himself from the anxiety and mental illness that can weaken his personality. In Islam’s view the child is a mandate imposed by Allah to his parents, therefore parents should keep the funds to maintain the mandate. Children from infancy to school age have a single environment, the family. So it is not surprising to say that the habits of children are largely formed by education in the family. From waking up to sleep again, children receive influence and education from the family environment.